Prenatal sonographic features of isolated hypoplastic left heart syndrome - Theera Tongsong (2018)
Hypoplastic left heart syndrome (HLHS) is a spectrum of fetal conditions associated with severe hypoplasia of the left ventricle and left ventricular outflow tract. The purpose of this series was to focus on the sonographic prenatal features of isolated HLHS. Based on the 5 cases presented here, the prenatal sonographic features of HLHS include small-sized left ventricle, atretic or hypoplastic mitral valves with restricted motion and a small amount of antegrade flow or regurgitation, and hypoplastic ascending aorta. Retrograde flow in the transverse aortic arch strongly suggests inadequate systemic output from the left heart. Tricuspid regurgitation is common and increases the chance for the development of hydrops. Other findings may be helpful, including left ventricular hyperechoic endocardium and increased nuchal translucency at 11-14 weeks. With careful fetal echocardiography, HLHS may be readily observed on a 4-chamber view as either a small or even absent left ventricle. © 2005 Wiley Periodicals, Inc.